A female head–neck model for rear impact simulations. (25th January 2017) - Östh, Jonas; Mendoza-Vazquez, Manuel; Sato, Fusako; Svensson, Mats Y.; Linder, Astrid; Brolin, Karin
Abstract: Several mathematical cervical models of the 50th percentile male have been developed and used for impact biomechanics research. However, for the 50th percentile female no similar modelling efforts have been made, despite females being subject to a higher risk of soft tissue neck injuries. This is a limitation for the development of automotive protective systems addressing Whiplash Associated Disorders (WADs), most commonly caused in rear impacts, as the risk for females sustaining WAD symptoms is double that of males. In this study, a finite element head and neck model of a 50th percentile female was validated in rear impacts. A previously validated ligamentous cervical spine model was complemented with a rigid body head, soft tissues and muscles. In both physiological flexion-extension motions and simulated rear impacts, the kinematic response at segment level was comparable to that of human subjects. Evaluation of ligament stress levels in simulations with varied initial cervical curvature revealed that if an individual assumes a more lordotic posture than the neutral, a higher risk of WAD might occur in rear impact. The female head and neck model, together with a kinematical whole body model which is under development, addresses a need for tools for assessment of automotive protection systems for the group which is at the highest risk to sustain WAD.